2020
DOI: 10.37219/2528-8253-2020-4-55
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory mechanisms in the action of the antiseptic drug lizak (clinical and immunological study)

Abstract: Topicality: In recent years, ideas about the mechanisms of action of a local lysozyme containing antiseptic have been significantly expanded. Data on the availability of antiviral drugs and a positive effect on regeneration processes have been obtained. Objective: In order to further study the properties of the drug, its effect on the mechanisms of inflammation in a clinical setting and model of inflammation in an animal experiment was investigated. Material and methods: Clinical and immunological studies were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 1 publication
1
1
0
Order By: Relevance
“…Thus, our experimental studies aimed to develop new approaches and technologies for vaccination against respiratory viruses, which enter mainly through the upper respiratory tract, confirm the concept of the feasibility of local intranasal vaccination against influenza and other respiratory viruses. The data obtained during the research on more effective appearance of protective local immunity both in terms of humoral immune response and interferon protection of the respiratory tract during intranasal vaccination coincide with the data of other authors [13,14]. In particular, based on their observations, Zheng Z et al predict that noninvasive vaccine administration will be more widely applied in the clinic in the near future [21].…”
Section: Content Of Antibodies To Hemagglutinin Of Influenza a And B Viruses In Different Immunization Typessupporting
confidence: 72%
See 1 more Smart Citation
“…Thus, our experimental studies aimed to develop new approaches and technologies for vaccination against respiratory viruses, which enter mainly through the upper respiratory tract, confirm the concept of the feasibility of local intranasal vaccination against influenza and other respiratory viruses. The data obtained during the research on more effective appearance of protective local immunity both in terms of humoral immune response and interferon protection of the respiratory tract during intranasal vaccination coincide with the data of other authors [13,14]. In particular, based on their observations, Zheng Z et al predict that noninvasive vaccine administration will be more widely applied in the clinic in the near future [21].…”
Section: Content Of Antibodies To Hemagglutinin Of Influenza a And B Viruses In Different Immunization Typessupporting
confidence: 72%
“…Kolomyichenko of the NAMS of Ukraine" developed the concept of local etiologically adequate vaccination, based on the statement that the vaccine should be administered in the same way as the infection, i.e. in cases of respiratory infections it should be intranasal or oral administration of vaccine material [9,14]. So, the aim of this work was to demonstrate the benefits of local vaccination against respiratory viruses, as well as the use of nanocarriers in such vaccination and possible cross-antigen reactions by hemagglutinin between antigens of influenza virus and severe acute respiratory syndrome-related coronavirus 2 (SARS-CoV-2).…”
Section: Abstract: Respiratory Viruses Local Immunity Nanoparticles Vaccination Conceptmentioning
confidence: 99%
“…Also, of practical perspective are studies on the effectiveness of Cinnabsin ® in adenoiditis treatment 27,28 . In addition to clinical studies, Cinnabsin ® was investigated in an experimental study, which showed its modulating effect on various parts of the immune system 29 . The data obtained in this study cannot be explained by the "placebo effect", which is sometimes attempted to explain the effectiveness of combined homeopathic remedies.…”
Section: Discussionmentioning
confidence: 99%